Perencanaan Metode Perawatan Pencegahan Kerusakan pada Mesin Ripple Mill Type KCM 6T - Muh Anhar; Sartika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2017)
Oil palm nut plantation and factory shows fluctuated development. One of the indicators is that the CPO (Cruid Palm Oil) cost is getting better. The rapid progress of science and technology currently influences the production process in factory so it becomes more effective and efficient. Specifically, Ripple Mill Type KCM 6T is a kind of high technology machine that is operated to crack palm fruit and separate the kernel from its shell. To keep the machine working in a good condition, it is a must to pay attention on the method to maintain it. Particular preventative maintenance method is needed to do to avoid some failures of the machine or engine so it can be used for longer time. Regular field survey needs to be done to collect concrete information about the latest condition of engine/ machine and the result of survey must be written down into control card and maintenance card. These cards can be reminder for the user to monitor the engine/ machine condition and as an effort to keep the cracker works optimally.